2012
DOI: 10.1007/s00249-012-0813-9
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based statistical analysis of transmembrane helices

Abstract: Recent advances in high-resolution structure determination of membrane proteins enable now the analysis of the main features of amino acids in transmembrane (TM) segments in comparison with amino acids in watersoluble helices. In this work, we introduced a large-scale analysis of amino acid propensities using a data set of 170 structures of integral membrane proteins obtained from MPTopo database and 930 structures of water-soluble helical proteins obtained from the Protein Data Bank. Large hydrophobic residue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
112
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(116 citation statements)
references
References 39 publications
4
112
0
Order By: Relevance
“…Helix ␣1 is slightly longer than expected for typical trans-membrane proteins found within the ER or Golgi (20 residues) (36). However, the N-terminal region of helix ␣1 (residues Glu-17-Trp-20, comprising the N-terminal capping motif) contains residues that are known to prefer the polar/nonpolar interface of lipid bilayers (32). These residues are partially flexible and solvent-exposed, suggesting that the N-terminal portion of ␣1 may protrude from the surface of the membrane.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Helix ␣1 is slightly longer than expected for typical trans-membrane proteins found within the ER or Golgi (20 residues) (36). However, the N-terminal region of helix ␣1 (residues Glu-17-Trp-20, comprising the N-terminal capping motif) contains residues that are known to prefer the polar/nonpolar interface of lipid bilayers (32). These residues are partially flexible and solvent-exposed, suggesting that the N-terminal portion of ␣1 may protrude from the surface of the membrane.…”
Section: Discussionmentioning
confidence: 91%
“…The data indicate that a disruption in the TMD ␣1 helix several residues upstream of Pro-32 around residues Ala-27-Leu-28 introduces some flexibility into the helix in this region. Proline residues are known to be helixdestabilizing in water-soluble proteins but are surprisingly common in trans-membrane proteins (32,37). They often introduce a region of flexibility and a kink in trans-membrane helices because of steric conflicts with the preceding residue and loss of a backbone hydrogen bond (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore designed 19-residue TM sequences that contain an equal number of polar and hydrophobic residues, nine Ser and nine Leu residues, each with a centrally positioned Trp residue as a fluorescent probe. As the most commonly occurring amino acid in native TM helices, Leu was a natural choice, 22 while Ser is the most commonly occurring polar residue (similar to Thr) and can participate in both side chain–side chain and side chain–backbone H-bonds. 22 In addition, synthesis requirements of β-branch-rich peptides rendered Thr as a less feasible choice.…”
Section: Resultsmentioning
confidence: 99%
“…While many studies addressing the formation of helical hairpins in membranes have been carried out on model hydrophobic TM segments, [6][7][8][9] naturally occurring helical hairpins are not always highly hydrophobic, 10 and the role of helix-helix interactions and turn propensities of the residues interconnecting the two helices in their folding and stability is poorly understood. We previously showed that poliovirus (PV) 2B, which is a small protein involved in PV virulence, is a double-spanning integral membrane protein, in which the two TM segments are interconnected by a short turn forming a putative helical hairpin.…”
Section: Introductionmentioning
confidence: 99%